(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
At present, the provision of food security in maintaining a healthy lifestyle remains largely dependent on the composition of fruits and vegetables. It is known that the excessive use of mineral fertilizers in increasing the yield of agricultural products increases the amount of nitrate in the composition of fruits and vegetables from the permissible norm. Also, the application of biological (green manure) fertilizer, which is an alternative to mineral fertilizers in the prevention of poisoning from nitrate, is considered acceptable in all respects